2022
DOI: 10.1371/journal.pone.0276976
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum indirect bilirubin levels and skeletal muscle mass in older male and female patients with type 2 diabetes

Abstract: Objective We previously showed that low serum bilirubin levels are associated with disability in quality of daily living in older patients with diabetes. However, the underlying mechanism is not fully understood. The aim of this study is to assess the relationship between serum bilirubin levels and skeletal muscle mass in older patients with type2 diabetes. Methods A total of 272 older patients with type2 diabetes (152 male and 120 female) aged 60 years and over were continuously recruited from April 2020 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Also there is some evidence to suggest that diabetes mellitus can increase apoptosis in the liver (Inoguchi et al, 2022). Some Studies have shown that high blood glucose levels in diabetes can activate a number of cellular pathways that contribute to apoptosis in liver cells, a chronic exposure to high glucose levels can lead to the activation of a protein called caspase-3, which is involved in the apoptotic pathway (Meisse et al,2002).…”
Section: Parametersmentioning
confidence: 99%
“…Also there is some evidence to suggest that diabetes mellitus can increase apoptosis in the liver (Inoguchi et al, 2022). Some Studies have shown that high blood glucose levels in diabetes can activate a number of cellular pathways that contribute to apoptosis in liver cells, a chronic exposure to high glucose levels can lead to the activation of a protein called caspase-3, which is involved in the apoptotic pathway (Meisse et al,2002).…”
Section: Parametersmentioning
confidence: 99%